Nitrogen-doped titanium dioxide as a hole transport layer for high-efﬁciency formamidinium perovskite solar cells - Pochont, Nitin Ralph; Sekhar, Yendaluru Raja; Kuraganti, Vasu; Jose, Rajan (MDPI, 2022)
Perovskite solar cells (PSCs) offer advantages over widely deployed silicon solar cells in terms of ease of fabrication; however, the device is still under rigorous materials optimization for cell performance, stability, and cost. In this work, we explore a version of a PSC by replacing the polymeric hole transport layer (HTL) such as Spiro-OMeTAD, P3HT, and PEDOT: PSS with a more air-stable metal oxide, viz., nitrogen-doped titanium dioxide (TiO2:N). Numerical simulations on formamidinium (FA)-based PSCs in the FTO/TiO2/FAPbI3/Ag configuration have been carried out to depict the behaviour of the HTL as well as the effect of absorber layer thickness (∆t) on photovoltaic parameters. The results show that the cell output increases when the HTL bandgap increases from 2.5 to 3.0 eV. By optimizing the absorber layer thickness and the gradient in defect density (Nt), the device structure considered here can deliver a maximum power conversion efficiency of ~21.38% for a lower HTL bandgap (~2.5 eV) and ~26.99% for a higher HTL bandgap of ~3.0 eV. The results are validated by reproducing the performance of PSCs employing commonly used polymeric HTLs, viz. Spiro-OMeTAD, P3HT, and PEDOT: PSS as well as high power conversion efficiency in the highly crystalline perovskite layer. Therefore, the present study provides high-performing, cost-effective PSCs using TiO2:N.